Implementation Of AI-Assisted Njombangan Visual Interactive Media As A Local Cultural Education For Children at KB Alfi Munir - Kinanti Erste Panggayuh Putri; Bentar Candra Perdana Perdana; Shabrina Fitria Az Zahra Zahra; Azzahra Maycca Yunizar Yunizar (Universitas AMIKOM Yogyakarta, 2026)
In the Early Childhood Education (PAUD) curriculum, the use of digital media in learning is necessary to adapt to technological developments and be able to create a mindful, meaningful, and joyful learning experience. However, KB Alfi Munir Jombang as an early childhood education institution is still dominated by conventional learning so it is not able to accommodate the characteristics of children as a digital native generation. This community service activity aims to improve the quality of learning through training and implementation of interactive visual learning media